Review: Control of Strawberry Aphids (Chaetosiphon Fragaefolii; Aphididae) Through Sustainable Natural Materials In Strawberry (Fragaria X Ananassa) Cultivation - Muhammad Muzayyin Arsyi; Henik Sukorini; Sri Mursiani Arifah (Green Publisher Indonesia, 2024)
Leaf aphid (Chaetosiphon fragaefolii; Aphididae) is one of the pests that attack Strawberry plants (Fragaria x ananassa) which can transmit infective viruses to Strawberry plants (Fragaria x ananassa). Symptoms caused by leaf aphids (Chaetosiphon fragaefolii) include sooty mold, dwarfed growth, twisted stems, curling, and yellowing. Farmers will suffer losses caused by the symptoms of leaf aphids (Chaetosiphon fragaefolii) such as significant decreases in Strawberry (Fragaria x ananassa) harvest yields. The methodology used in this article review is by conducting literature studies from various platforms such as Google Scholar, Science Direct, Bing AI, Publish or Perish, and SINTA from the Ministry of Education and Culture. The literature obtained consists of 60 journals discussing leaf aphids (Chaetosiphon fragaefolii) attacking Strawberry plants (Fragaria x ananassa), symptoms caused by leaf aphids (Chaetosiphon fragaefolii), and leaf aphid (Chaetosiphon fragaefolii) control methods. Then the literature obtained is summarized and organized using Mendeley. The aim of this literature study is to examine ways to control leaf aphids (Chaetosiphon fragaefolii) attacking Strawberry plants (Fragaria x ananassa) using natural materials. The results for controlling leaf aphids (Chaetosiphon fragaefolii) through natural materials are as follows: Entomopathogenic fungi: Beauveria bassiana and Metarhizium sp. Parasitoids: Aphelinus varipes, Predators: Syrphidae family, Asilidae family, Orius insidiosus, Cycloneda sanguinea, Eriopis connexa, and Coleomegilla quadrifasciata. Organic pesticides: neem leaves with a concentration of 35 (g/l of water) and mortality of 8.76 individuals, while papaya leaves using a concentration of 30 ml/liter of water.